Ermenistan’ın Etnik Temizlik, Soykırım ve Işgalcilik Politikasının Sonuçları - Ahmedov, Elçin (Fırat University, 2013)
Historical information shows that the transfer of a large number of Armenians from Iran and Turkey to mountainous Karabakh, a strategically important region of Azerbaijan, started in the early nineteenth century. This transfer process continued as part of colonial policy of the Tsarist Russia throughout the nineteenth century and ultimately affected the demographic change in the region. Artificial increasing the number of Armenians in this region let them start their territorial claims against Azerbaijan in the early twentieth century. The article idicates that over the last 200 years Azerbaijani people being subjected to ethnic cleansing, genocide and aggression policy being deported from their native land became refugee and IDPs. At the same time, according to the facts the article analyses aggression policy of Armenia against Azerbaijan which was supported by the ruling circles of the Soviet Union. Armenians carried out ethnic cleansing, genocide and aggression policy against Azerbaijanis and forced them to leave their own lands and turned them to refugees. At the same time, in the article at the end of the XX century genocide committed in Khojaly by Armenians is estimated one of the most terrible crimes committed against humanity and mankind.
The Results of Ethnic Cleaning, Genocide and Aggression Policy of Armenia